THE ANALYSIS OF BPJS PATIENT SATISFACTION LEVEL OF THE QUALITY HEALTH SERVICES IN PAFIO B ROOM CIBINONG HOSPITAL: ANALISIS TINGKAT KEPUASAN PASIEN BPJS TERHADAP MUTU PELAYANAN KESEHATAN DI RUANG PAFIO B RSUD CIBINONG - Deden Nurjaman; Dede Rukasa (Wijaya Husada, 2019)
Satisfaction is feeling happy or disappointed someone who emerged after comparing the perception or impression of the performance or the result of a product or expectations. Good quality will increase customer satisfaction, according to law number 36 of 2009 on health stressed the importance of improving the quality of health services. This study aims to determine how the level of patient satisfaction BPJS to quality health care in the space Pafio B Cibinong General Hospital. This research method using cross sectional method using Kendall Tau Correlation. And the method of taking samples in this study with Probability Sampling technique with the number of sample of 170 respondents. The results showedas many as 97 respondents (57.1%) reported better quality of health care, 84 of them said they were satisfied. While 73 respondents (42.9%) stating quality of health care is not good, of which 71 respondents (41.8%) are not satisfied. Based on the results obtained by p value = 0,000 with significant value <0.05. There is a relationship between the quality of health care with patient satisfaction level in the room BPJS Pafio B Cibinong General Hospital.